Modelagem agrometeorológica da cana-de-açúcar nas condições edafoclimáticas do centro-oeste goiano - Caetano, Jordana Moura (2017)
Brazil is the worlds largest producer of sugarcane and its derivatives (sugar and ethanol). Due to the growing demand of these products, there has been a constant expansion of land with sugarcane in the country, mainly in the state of Goiás, which currently has the second largest harvest and production crop area countrywide. Considering its complex production system, which involves different growing environments (climate and soil), the characterization of the growth, development and maturation of sugarcane is one of the most fundamental aspects for determining the quality and quantification of the raw material, besides assisting in the planning of harvesting activities. In tropical (hot) regions, such as midwest Goiás, the reduction of grown and development rates and the process of accumulation in soluble solids of stems occurs mainly as a function of soil water deficit and atmospheric water demand. The quantification of these responses from the crop to the environment can be estimated by mathematical models generated as a function of agrometeorological and soil water variables. A mathematical model was used as a tool for estimating grown development and plant production, also the agricultural sector has benefited from these models of crop forecasting. However, the estimate of soluble solids accumulation in sugarcane still requires studies since the knowledge of the procedure that involves interaction of the agrometeorological conditions and the physiological responses of the crop is insufficient. Thus, the objectives of this research were: characterization of the biometric behavior and soluble solids content of sugarcane in response to the natural environment and soil conditions of the midwest region of Goiás, identification of the water depth in the soil that causes the reduction of growth rates and development of the crops that contributes to the accumulation of soluble solids in the stems, creation of empirical models for the determination of biometric parameters and the soluble solids content of the plant in response to the growing time and agrometeorological variables, elaboration of multiple linear regression models of soluble solids content, (°Brix) and total recoverable sugars (ATR, kg t-1 ) due to the agrometeorological variables and water depth in the soil to obtain the estimation errors of the models and their validation. The following shows the research stucture: after the general introduction and bibliographic review on the subject, the first article presents the characterization and trend of behavior of the grown and development of sugarcane for the environment conditions and soil water table in midwest Goiás, and the second article shows agrometeorological models generated for the estimation of soluble solids (°Brix) and total recoverable sugars (ATR, kg t-1 ) in order to use them as an alternative of estimation in crop environments similar to the conditions that were generated.